The monks of the Nag Hammadi codices: contextualising a fourth-century monastic community - Tutty, Paula (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025, 2025)
This work tells the story of a community of fourth-century monks living in Egypt. The letters they wrote and received were found within the covers of works that changed our understanding of early religious thought - the Nag Hammadi Codices. This book seeks to contextualise the letters and answer questions about monastic life. Significantly, new evidence is presented that links the letters directly to the authors and creators of the codices in which they were discovered